Implementation of Religious Values Through Mothers' Study Activ-ities in Family Empowerment in Pandan District - Amriansyah Pohan; Ananda Yukhairiza Simatupang; Lidia Kusmira; Zulhimma Zulhimma; Yona Riska Amelia (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
Women's religious study activities are a form of non-formal religious education that plays a strategic role in the internalization of religious values within the family. This study aims to describe and analyze the implementation of religious values through women's religious study activities and their contribution to family empowerment in Pandan District. This study applies a qualitative approach with descriptive methods. This approach is used to obtain an in-depth picture of the social reality related to the application of religious values in women's religious study activities . The study was conducted in Pandan District with subjects including religious study administrators, female religious teachers , and members of women's religious study activities as referred to by Sugiyono (2019). Data collection was conducted through in-depth interviews with 10 respondents to obtain information related to the implementation process and the impact of religious study activities. Direct observation was also conducted to observe the course of activities. Data analysis was carried out in stages through the process of data reduction, data presentation, and drawing conclusions in accordance with the Miles and Huberman analysis model. The research results show that women's religious study activities serve not only as a means of increasing religious understanding but also as a means of strengthening women's roles in fostering religious, harmonious, and independent families. The continuous implementation of religious values has an impact on improving the spiritual, social, and economic quality of families.